INTERPRETASI TERM BA’ÛDHATAN FAMÂ FAUQAHÂ PERSPEKTIF AL-TAFSÎR AL-TARBAWÎ DAN AL-I’JÂZ AL-‘ILMÎ - Rahendra Maya; Muhammad Fadilah Alfarisi; Hidayati Hidayati (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
Even thought it is only found in one verse in one letter, the parable about small animals and other animals like them has attracted great attention in the form of research. In this case, Allah is not ashamed and even makes it an example (matsal) in the Al-Qur’an, namely in Surah Al-Baqarah [2]: 26. In this verse, the animal used an example is contained in the term ba’ûdhatan famâ fauqahâ. Therefore, this article attempts to examine the interpretation of the verse, especially the interpretation of the term ba’ûdhatan famâ fauqahâ in it, based on the perspective of al-tafsîr al-tarbawî and al-i’jâz al-‘ilmî. This research uses a type of qualitative research with a literature or library study approach combined with the thematic interpretation method (tafsîr maudhû’î) because it examines the interpretation of shcolar moslem towards verses of the Al-Qur’an. The data collection technique uses documentary technique, while the data analysis uses decriptive interpretative content analysis technique. The result of the research show that in general, based on the opinion of the majority of shcolar moslem, the term ba’ûdhatan famâ fauqahâ is interpreted as mosquitoes (ba’ûdhah) and other animals that are smaller than if (famâ fauqahâ), including in the perspective of al-tafsîr al-tarbawî and al-i’jâz al-‘ilmî. What is distinctive, in al-i’jâz al-‘ilmî’s perspective, which is more widely revealed is the aspects of miracle as creatures created by Allah that deserve high attention to be more aware in drawing closer to Him, especially when used as an example.